Pemetaan Karakteristik Permukiman Kumuh Pesisir Untuk Pengelolaan Bencana di Makassar (Universitas Muslim Indonesia, 2016)
Makassar is one of the cities that most of the region is an area of ​​coastal settlements.But climate change is happening constantly in the coastal settlements, causing floods, high winds and waves of the flood, which at any moment threatens homes located area of ​​coastal settlements. This will affect the economic viability and sustainability of life in the region. The purpose of this study was to identify the characteristics of coastal settlements for disaster management in the coastal area of ​​the city of Makassar, so that life can continue. Generally, this research is descriptive-evaluative using two approaches, Behaviour and Architectural Approach Appproach(Neer,1999).The first approach deals with the study of the process of resettlement of residents,